A global history of gold rushes - Mountford, Benjamin, 1980-; Tuffnell, Stephen, 1987- (California world history library ;, 2018)
"Nothing set the world in motion like gold. Gold rushes accelerated the global circulation of people, goods, capital, and technologies that transformed settler societies around the world. Yet, they are rarely considered in a global perspective. While in the past national histories have emphasized the role of gold rushes as accelerants of state formation, crucibles of national character, and watersheds of political development, the essays in Gold Rush begin from a different premise. They explore gold rushes as connected phenomena and emphasize the destructive power of the search for gold on Indigenous communities and the environment, and their role as incubators of racial hierarchy and immigration restriction. The essays in Gold Rush showcase the best and most current research methodologies in global history - comparative, environmental, and transnational - to address these concerns. Gold Rush uses diverse themes and places as vantage points on the nineteenth century gold rushes - from the catalytic effect of the discovery of California placer gold in 1848 to the nostalgic rush to the beaches of Nome, Alaska, fifty years later; from anxious commentators discussing the public good and disorder of gold mining in Georgia, California, and Victoria to the worldwide discussion of the "Chinese Question" and the productivity of non-white labor in Africa; from the assertion of corporate control over lode mining to the destructive environmental and financial consequences of that control. At the heart of this book is the paradoxical power of gold rushes to connect and divide, to enrich and impoverish, to create and destroy"--Provided by publisher.